Reclassification on a grand scale; Moys at the BLL - Bird, R (Cambridge University Press, 2010)
In 2006 staff at the Bodleian Law Library commenced the process of reclassifying our entire current monograph collection to the Moys Scheme. In this article the reasons for selecting Moys, the issues involved, and the progress to date are discussed.